A Series of Ternary Metal Chloride Superionic Conductors for High‐Performance All‐Solid‐State Lithium Batteries. Issue 21 (7th April 2022) - Liang, Jianwen; van der Maas, Eveline; Luo, Jing; Li, Xiaona; Chen, Ning; Adair, Keegan R.; Li, Weihan; Li, Junjie; Hu, Yongfeng; Liu, Jue; Zhang, Li; Zhao, Shangqian; et al.
Abstract: Understanding the relationship between structure, ionic conductivity, and synthesis is the key to the development of superionic conductors. Here, a series of Li3‐3 x M1+ x Cl6 (−0.14 < x ≤ 0.5, M = Tb, Dy, Ho, Y, Er, Tm) solid electrolytes with orthorhombic and trigonal structures are reported. The orthorhombic phase of Li–M–Cl shows an approximately one order of magnitude increase in ionic conductivities when compared to their trigonal phase. Using the Li–Ho–Cl components as an example, their structures, phase transition, ionic conductivity, and electrochemical stability are studied. Molecular dynamics simulations reveal the facile diffusion in the z ‐direction in the orthorhombic structure, rationalizing the improved ionic conductivities. All‐solid‐state batteries of NMC811/Li2.73 Ho1.09 Cl6 /In demonstrate excellent electrochemical performance at both 25 and −10 °C. As relevant to the vast number of isostructural halide electrolytes, the present structure control strategy guides the design of halide superionic conductors. Abstract : A favorable orthorhombic phase in various Li–M–Cl (M = Dy, Ho, Y, Er, Tm) systems which triggers a significant increase in Li + diffusivity and reduces the activation energy barrier for diffusion is revealed. The findings are expected to aid the discovery of fundamental chemical theories relating to the activity of rare earth metal halides and exploration of new materials with high Li + conductivity.